PEMANFAATAN ABU BAGASSE SEBAGAI FILLER TERHADAP NILAI MARSHALL TEST PADA CAMPURAN ASPHALT TREATED BASE ( ATB ) - Andi Syaiful Amal (Media Teknik Sipil, 2011)
Solidity construction of road of Indonesia generally are flexible solidity construction. One ofkind flexible solidity are solidity of ATB ( Asphalt Treated Base ) layer that give fundamental layerfunction that under surface layer which support and spread load along with place to put surfacelayer. Trial to asphalt are follow : penetration, flexible point, ductility, while trial of agregate follow: kind heavy ang agregate absorption, analysis of agregate filler. The thing of test trial of optimumasphalt degree is devided 5 variation namely 5%, 5.5%, 6%, 6.5% and 7% wich each groups aremade 5 different sample with weight each 1200 gram. The optimum asphalt degree which be got6.5%. The thing of test trial of optimum asphalt by filler Bagasse Dust are made 11 groups by fillerdegree 6.42% early which be made 0% up to 90% of Bagasse dust according to weight with 10%interval, by each groups are made 3 samples. The study result showed that three are influence ofusing Bagasse dust as filler to Marshall Test value. Stability is shown by equation Y = 1672.5 +17.544 X – 0.2336 X2 gotten optimum Bagasse dust degree about 37.59% by stability value are2001.033 kg. The flow value is shown by equation Y = 4.05 + ( 2.7 E – 3 ) X – ( 1 E – 4 ) X2 byoptimum Bagasse dust degree about 13.5% is gotten flow value 4.05%. The hole in ATB compoundis shown by equation Y = 4.102 + ( 0.04 ) X – ( 5 E – 4 ) X2 is gotten optimum Bagasse dust about40% by air hole about 4.90%. To Marshall Quotient value may be shown by equation Y = 4.007 +( 0.046 ) X – ( 5 E – 4 ) X2 by optimum Bagasse dust degree about 46% by Marshall Quotient valueare 5.06 kN/mm.Key word : Asphalt Treated Base ( ATB ), Bagasse Dust.